KONTRIBUSI KOMUNIKASI INTERNAL TERHADAP KINERJA PEGAWAI DINAS PERHUBUNGAN KOMUNIKASI DAN INFORMATIKA KABUPATEN TASIKMALAYA - Sahwa Sekar Dini; Agus Fatah Hidayat; Basuki Rahmat (Jurnal Progress Administrasi Publik, 2026)
This study is motivated by the importance of internal communication in improving employee performance within public sector organizations. Several issues were identified at the Department of Transportation, Communication and Informatics of Tasikmalaya Regency, including delays in information delivery, limited communication interaction between leaders and employees, and the lack of opportunities for employees to express ideas. This study aims to analyze the contribution of internal communication to employee performance in the context of public organizations. This research employs a quantitative method with an associative approach. The sampling technique used is saturated sampling, involving all 74 employees as respondents. Data were collected through questionnaires and analyzed using simple linear regression analysis and t-test to examine the research hypothesis. The results indicate that internal communication has a positive and significant effect on employee performance, with a coefficient of determination of 23.6%, while the remaining 76.4% is influenced by other factors beyond the scope of this study. These findings suggest that internal communication plays an important role in improving employee work effectiveness, although it is not the only determining factor. The scientific contribution of this study lies in examining internal communication specifically within the context of local government organizations, particularly at the Department of Transportation, Communication and Informatics of Tasikmalaya Regency, by emphasizing vertical and horizontal communication patterns in supporting employee performance.   Keywords: Employee Performance; Internal Communication; Public Organization